2011
DOI: 10.1097/hp.0b013e3181f1e9b5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Staff Finger Doses During Quality Control of FDG Production

Abstract: The European Pharmacopoeia and Good Manufacturing Practice define a number of quality control tests that must be performed prior to the release of FDG. The aim of this study is to determine the finger dose received while performing these tests. The finger dose received by four staff members was measured using Unfors NED monitors placed at the tip of the index finger of both hands during routine quality control. A total of 18 readings were obtained for the dispensing of the quality control samples, bubble point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Conventional QC tests require an array of expensive analytical instrumentation, all of which requires space, maintenance, training, calibration, and documentation, making such testing a time-consuming, expensive procedure 49 , 62 . Furthermore, some of the tests require manual handling of the radioactive batches resulting in high radiation exposure to the operator 63 and higher margin for human error or subjective interpretation. Moreover, pairing a compact microfluidic reactor system with a large analytical laboratory facility undermines the economic and practical advantages offered by microfluidic technology.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional QC tests require an array of expensive analytical instrumentation, all of which requires space, maintenance, training, calibration, and documentation, making such testing a time-consuming, expensive procedure 49 , 62 . Furthermore, some of the tests require manual handling of the radioactive batches resulting in high radiation exposure to the operator 63 and higher margin for human error or subjective interpretation. Moreover, pairing a compact microfluidic reactor system with a large analytical laboratory facility undermines the economic and practical advantages offered by microfluidic technology.…”
Section: Discussionmentioning
confidence: 99%
“…If the bubble point exceeds a threshold pressure, then it can be assured that the membrane is intact and pores do not exceed the specified size. A drawback of this test is that the operator has to manually handle the filter membrane and it has been reported that this test results in the largest radiation dose to QC personnel [ 18 ].…”
Section: Miniaturization Of Quality Control Testsmentioning
confidence: 99%
“…In addition, for most tests, manual handling, loading, and/or visual assessment of samples leads to significant radiation exposure to personnel and operator-induced variability in the results. In particular Ferguson et al found that QC personnel received significant radiation exposure, especially due to performing sterility (filter integrity), pH, and chemical/radiochemical purity and identity testing [ 18 ]. Furthermore, in contrast to ordinary pharmaceuticals, each batch of short-lived PET radiopharmaceuticals has to be manufactured and tested within a short period of time to prevent significant losses due to radioactive decay [ 17 ].…”
Section: Introductionmentioning
confidence: 99%